Raw data of continuous Sentinel ADCP at 150m May-June 2021 in front of Cape St. Vincent, Sagres PT - Relvas, Paulo; Mendes de Sousa, Carlos; Rautenbach, Sarah (PANGAEA, 2023)
Until today the availability of continuous and long-term in-situ data of ocean currents is sparse. Yet, in-situ observations play a major role in understanding ocean dynamics and can be used for various purposes.Therefore, continuous and long-term time series are highly valuable for the scientific community and decision makers. In the frame of the European Multidisciplinary Seafloor and water column Observatory (EMSO-ERIC) an acoustic-doppler current profiler was deployed at 150 m depth at the edge of the continental slope, 10 nm south of Cape St. Vincente, the SW tip of the Iberian Peninsula (36.8484, -8.9270) from May - June 2021. This dataset contains raw data, collected with a Teledyne RDI Sentinel V100 300 kHz Acoustic Doppler Current Profiler (ADCP), mounted in a upward facing subsurface buoy with 51 bins á 3m each and a blank of 2m. Number of pings 100. Ping interval 5.00 s.
Keywords: ADCP; ADCP data; Coastal; current; Current Direction; currents; current velocity; Iberian margin; Iberian Peninsula; marine; ocean; oceanographic moorings; oceanography; Physical oceanographic data; physical oceanography; Portugal; Temperature; Time series